PEMAHAMAN PERATURAN PAJAK, PELAYANAN APARAT PAJAK DAN DAMPAKNYA TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERATING (Studi kasus wajib pajak KPP Kalideres Jakarta Barat) - Syamsurizal Syamsurizal (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The tax contribution for the development of the country is crucial so it needs to be analyzed more deeply the influence of the understanding of the tax regulation and the service of the tax authorities moderated by the risk preference to taxpayer compliance registered at Tax Office (KPP) Kalideres West Jakarta. The data used is the primary data by distributing questionnaires to the Mandatory registered in the Primary Tax Office (KPP) Pratama Kalideres West Jakarta. The population that will be the object of research are all taxpayers registered in the Primary Tax Office (KPP) Pratama Kalideres West Jakarta until the period of December 2016. The sampling technique used is accidental sampling. This research uses multiple lininer regression method. The results showed that the understanding of tax rules have a positive and significant effect on the taxpayers' lalowkdge and service of tax officials positive and significant to taxpayer compliance. The results of this study also conclude that the effect of understanding tax regulations on taxpayer compliance is not moderated significantly by risk preferences.